On the Asymmetrical Sensitivity of the Distribution of Real Wages to Business Cycle Fluctuations - Rodrigo Barrela; Eduardo Costa; Pedro Portugal (Institute of Labor Economics (IZA), 2024)
We provide evidence showing, for the first time, that the sensitivity of real wages to the business cycle is much stronger for higher-wage workers than for lower-wage workers. Using matched employer-employee data for Portugal covering the period 1986-2021, we show that a one percentage point increase in the unemployment rate is associated with a decrease in real hourly wages of workers in the 90th percentile of the conditional wage distribution of around 1.3%, contrasted with 0.8% for those in the 10th percentile. This gap is even larger for newly hired workers – the estimates for the 90th percentile workers are double of those in the bottom decile. This pattern also holds for bargained wages and the wage cushion. These results can be explained by composition effects and heterogeneous sensitivities of firms and collective bargaining agreements (CBAs) to the cycle. First, the considerable gap in new hires' cyclicality arises mostly from match quality fluctuations over the business cycle and is sharply attenuated after we account for job match composition. Second, by estimating cyclicality coefficients for each firm/CBA, we find that firms and CBAs tend to provide a lower degree of insurance against aggregate cyclical fluctuations to higher paid individuals. These findings provide strong empirical evidence on the role of business cycles as amplifiers of inequality trends.
Keywords: E24; E32; J64; 330; wage cyclicality; quantile regressions; match quality; collective bargaining agreements